Measuring Education Pluralism Globally - Wodon, Quentin (Taylor and Francis, 2021)
In education systems that support pluralism, students or parents can choose the type of school or university they attend. Given heterogeneity in priorities for what should be taught, education pluralism has a value in itself. It may also boost schooling and learning. The fact that there is heterogeneity is clear, otherwise we would not have different types of schools. What is less clear is the extent to which education systems are pluralistic. Rather than looking at inputs for pluralism such as laws and regulations, this article introduces a measure of education pluralism based on outputs, i.e. enrollment in different types of schools and universities. The normalized education pluralism index is inspired by the literature on market concentration. Estimates are provided based on data for public, private non-Catholic, and Catholic institutions.